(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
A walking support system with phosphenes for blind people has been investigated. Phosphene is a phenomenon where a flash of light is recognized in the brain by giving an electrical stimulus to human’s visual pathway. Phosphenes can be perceived even if their eyes are closed or they are blind. It has been clarified that phosphenes can be induced to several directions if electrodes placements are precisely selected. When phosphenes are presented to two directions for recognizing two obstacles, two pairs of electrodes must be applied. In such a case, however, the electrical interference occurs due to the short distance between electrodes. In the practical use of the phosphene-based walking support system, the avoidance of electrical interference is significant in order to present the phosphenes precisely. Therefore, in this paper, we first practically investigate the electrical interference by considering the difference in phosphene induction generated by a single pair of electrodes and by two pairs of electrodes. Then, the solutions to avoid the electrical interference are discussed.